2001
DOI: 10.1021/jf0015120
|View full text |Cite
|
Sign up to set email alerts
|

Liver Injury Suppressing Compounds from Avocado (Persea americana)

Abstract: To evaluate the protective activity of fruits against liver injury, 22 different fruits were fed to rats with liver damage caused by D-galactosamine, a powerful liver toxin. As measured by changes in the levels of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST), avocado showed extraordinarily potent liver injury suppressing activity. Five active compounds were isolated and their structures determined. These were all fatty acid derivatives, of which three, namely, (2E,5E,12Z,15Z)-1-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 12 publications
3
56
0
Order By: Relevance
“…GalN is one such drug and has often been used to screen hepatoprotective foods, medicines or their constituents. We have demonstrated that GalN-induced liver injury was effectively suppressed by green tea (31)(32)(33), mushrooms (34), fruits (2), and dietary fibers (33) in rats. It has been thought that GalN induces liver injury by inhibiting the synthesis of RNA and proteins through a decrease in hepatic UTP concentration, which finally evokes the necrosis of liver cells (35)(36)(37), although recent reports have suggested that several cytokines, e.g., interleukin (IL)-1␣ (38), IL-6 (39) and IL-18 (40), and NO (41) might also participate in the pathogenesis of GalN-induced liver injury.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…GalN is one such drug and has often been used to screen hepatoprotective foods, medicines or their constituents. We have demonstrated that GalN-induced liver injury was effectively suppressed by green tea (31)(32)(33), mushrooms (34), fruits (2), and dietary fibers (33) in rats. It has been thought that GalN induces liver injury by inhibiting the synthesis of RNA and proteins through a decrease in hepatic UTP concentration, which finally evokes the necrosis of liver cells (35)(36)(37), although recent reports have suggested that several cytokines, e.g., interleukin (IL)-1␣ (38), IL-6 (39) and IL-18 (40), and NO (41) might also participate in the pathogenesis of GalN-induced liver injury.…”
Section: Discussionmentioning
confidence: 95%
“…It is widely recognized that relatively high intakes of fruits and vegetables are desirable for prevention of diseases and maintenance of healthy conditions ( 1 ). Previously we reported that several kinds of fruit had suppressive effects on D -galactosamine (GalN)-induced liver injury in rats when various kinds of lyophilized fruit were added to the diet ( 2 ). Furthermore, recently we found that some fruit juices, e.g., camu-camu and shekwasha, also had suppressive effects on GalNinduced liver injury in rats, and we identified the active compound (unpublished data).…”
mentioning
confidence: 84%
“…Moreover, some tropical and subtropical foodstuffs have been shown to have a strong suppressing effect on carcinogenesis and liver injury. 16,17) Therefore, tropical and subtropical plants may be attractive sources of functional foods beneficial to human health.…”
mentioning
confidence: 99%
“…These compound classes may be divided into alkanols (also sometimes termed "aliphatic acetogenins"), terpenoid glycosides, various furan ring-containing derivatives, flavonoids, and a coumarin. The highly functionalized alkanols [218,[219][220][221] of avocado have exhibited quite diverse biological properties thus far. For example, Oberlies et al isolated 1, 2, 4-trihydroxyheptadec-16-ene, 1, 2, 4-trihydroxyheptadec-16-yne , and 1, 2, 4 -trihydroxynonadecane from the unripe fruits of P. americana, and found these substances to be moderately cytotoxic when evaluated against a small panel of cancer cell lines [219].Kawagishi et al isolated 5 alkanols from avocado fruits with "liver suppressing activity" (as determined by the changes in plasma levels of alanine aminotransferase and aspartate aminotransferase), including compounds 9-11 [221] Avocado has sometimes received the reputation as a fruit too high in fat.…”
Section: Persea Americanamentioning
confidence: 99%